The Designation of Marine Protected Areas A Legal Obligation - von Rebay, Anna. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides empirical evidence that all States have a universally binding obligation to adopt national laws and international treaties to protect the marine environment, including the designation of Marine Protected Areas. Chapter by chapter this obligation is detailed, providing the foundation for holding States responsible for fulfilling this obligation. The fundamentals are analysed in a preliminary chapter, which examines the legally binding sources of the Law of the Sea as well as its historical development to help readers understand the key principles at hand. The Law of the Sea provides more than 1000 instruments and more than 300 regulations concerning marine protection. While the scope of most treaties is limited either regarding species, regions or activities, one regulation addresses States in all waters: the obligation to protect and preserve the marine environment as stipulated under Art. 192 of the 1982 United Nations Convention on the Law of the Sea (UNCLOS). As this 'Constitution of the Ocean' not only contains conventional laws but also very broadly reflects pre-existing rules of customary international law, an extensive analysis of all statements made by States in the UN General Assembly, their practices, national laws and regulations as well as other public testimonials demonstrates that Art. 192 UNCLOS indeed binds the whole community of States as a rule of customary international law with an erga omnes effect. Due to the lack of any objections and its fundamental value for humankind, this regulation can also be considered a new peremptory norm of international law (ius cogens). While the sovereign equality of States recognises States' freedom to decide if and how to enter into a given obligation, States can also waive this freedom. If States accepted a legally binding obligation, they are thus bound to it. Concerning the specific content of Art. 192 UNCLOS, a methodical interpretation concludes that only the adoption of legislative measures (national laws and international agreements) suffices to comply with the obligation to protect and preserve the marine environment, which is confirmed by the States' practices and relevant jurisprudence. When applied to a specific geographical area, legislative measures to protect the marine environment concur with the definition of Marine Protected Areas. Nonetheless, as the obligation applies to all waters, the Grotian principle of the freedom of the sea dictates that the restriction of activities through the designation of Marine Protected Areas, on the one hand, must be weighed against the freedoms of other States on the other. To anticipate the result: while all other rights under the UNCLOS are subject to and contingent on other regulations of the UNCLOS and international law, only the obligation to protect and preserve the marine environment is granted absolutely - and thus outweighs all other interests.
Introduction -- Setting the Scene -- Legally Binding Obligation -- Personal Scope - An Obligation Erga Omnes -- Geographical Scope - Marine Environment -- Substantive Scope - Designation of MPAs -- Special Regulations -- Conclusion and Summary in Theses.
Keywords: Law of the sea; International law; Aeronautics -- Law and legislation; Environmental law, International; Law of the Sea, Air and Outer Space; Sources and Subjects of International Law, International Organizations; International Environmental Law; Public International Law